Preparation method and application of composite additive for fracturing acidification
By using composite additives prepared by the ratio of composite surfactant and metal sol coated with modified nanomagnesium hydroxide whiskers in acid-fracting technology, the problems of surface tension and interfacial tension reduction and environmental pollution in the prior art are solved. , achieving efficient demulsification and discharge assistance effects.
Patent Information
- Application Number
- CN202410571341.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-09
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-05-09
AI Technical Summary
The additives in the existing acid fracturing technology have single performance, which cannot effectively reduce surface tension and interface tension, and there are environmental pollution problems.
The ratio of modified nanomagnesium hydroxide whiskers coated with composite surfactant and metal sol is used to prepare composite additives for fracturing and acidification by stirring and mixing, reducing the surface tension and interfacial tension of the system, and improving the demulsification and discharge rate.
It has achieved efficient reduction of surface tension and interface tension, improved demulsification and discharge rate, and has biodegradability and low pollution characteristics, which significantly improved the effect of fracturing and acidification treatment.
Smart Images

Figure BDA0004831013530000121 
Figure BDA0004831013530000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oilfield chemical additives, and in particular relates to a preparation method and application of a composite additive for fracturing and acidizing. Background Art
[0002] Acid fracturing technology is an organic combination of fracturing technology and acidizing technology. It can give full play to the advantages of both and better adapt to the transformation of oil reservoirs, so as to alleviate the damage to the formation caused by drilling and completion engineering, and thus achieve the purpose of increasing oil and gas production. According to different usage technologies, it can be divided into three categories: acid fracturing, acidizing, and acid washing. According to different solutions, it can be divided into ordinary acidizing, ordinary acidizing, and mixed acid acidizing.
[0003] Acid fracturing technology is an offensive technology to achieve increased production in oil and gas fields. It can significantly increase the production of oil and gas wells and is the main technical means for major oil fields to achieve increased and stable production. During the fracturing construction process, in order to ensure the construction effect, high-performance demulsifying and drainage agents such as drainage agents, demulsifiers, clay stabilizers, etc. are often added to the acid fracturing treatment fluid. The addition of additives can reduce capillary resistance and prevent the accumulation of working fluid from causing blockage of the formation.
[0004] At present, the additives disclosed in the prior art have defects such as single performance, inability to effectively reduce surface tension and interfacial tension, or multiple chemical components that easily cause environmental pollution. Therefore, developing an additive with strong demulsification ability and environmental friendliness is still the current research direction. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a preparation method and application of a composite additive for fracturing and acidizing. The composite additive for fracturing and acidizing of the present invention can reduce the surface tension and interfacial tension of the system and improve the demulsification and drainage rate.
[0006] The purpose of the present invention and the solution to the technical problem are achieved by adopting the following technical solutions.
[0007] One aspect of the present invention provides a method for preparing a composite additive for fracturing acidizing, the method comprising the following steps:
[0008] The composite surfactant, the metal sol-coated modified nano magnesium hydroxide whisker and deionized water are mixed in a mass ratio of 1:0.5 to 1:1 to 3, stirred at 30 to 40° C. for 1 to 2 hours, then cooled to room temperature, and organic alcohol is added and stirred to mix uniformly to obtain the composite additive for fracturing acidification;
[0009] Wherein, the amount of the organic alcohol added is 0.1 to 0.3 times the mass of deionized water;
[0010] The preparation process of the composite surfactant is as follows:
[0011] Dispersing humic acid and organosilicon monomer in a mass ratio of 1:1-2 in an acetone solution with a volume fraction of 10-30%, and then stirring and reacting at 100-150° C. for 4-8 hours under the action of an initiator and a stabilizer to obtain a humic acid / organosilane graft copolymer;
[0012] The humic acid / organosilane graft copolymer and the N-fatty acyl amino acid surfactant are mixed in a mass ratio of 1:1-3, and stirred at 100-120° C. for 1-4 hours to obtain a composite surfactant.
[0013] In a preferred embodiment of the present invention, the humic acid is prepared by mixing lignite with 30-60wt% potassium hydroxide solution in a mass volume ratio of 1g:10-20mL and reacting at 70-90°C for 2-5h.
[0014] In a preferred embodiment of the present invention, the silicone monomer is selected from one or a mixture of two or more of methyltriethoxysilane, methyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, n-butyltrimethoxysilane, n-butyltriethoxysilane, isobutyltriethoxysilane and isobutyltrimethoxysilane.
[0015] In a preferred embodiment of the present invention, the initiator is selected from one or a mixture of two or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutyramidine hydrochloride, and azobisisobutylimidazoline hydrochloride.
[0016] In a preferred embodiment of the present invention, the added amount of the initiator is 0.01 to 0.03 times the mass of humic acid.
[0017] In a preferred embodiment of the present invention, the stabilizer has a number average molecular weight of 1×10 6 ~5×10 6 Polyvinyl pyrrolidone between.
[0018] In a preferred embodiment of the present invention, the amount of the stabilizer added is 0.002 to 0.004 times the mass of humic acid.
[0019] In a preferred embodiment of the present invention, the N-fatty acyl amino acid surfactant is any one of fatty acyl lysine, fatty acyl arginine, and fatty acyl histidine with a carbon number between 4 and 16, or a mixture of two or more thereof.
[0020] In a preferred embodiment of the present invention, the preparation process of the metal sol-coated modified nano magnesium hydroxide whiskers is:
[0021] The basic magnesium sulfate whiskers are uniformly dispersed in deionized water, and then anhydrous ethanol and polyethylene glycol are added in sequence and mixed evenly, and then placed in a high-pressure reactor, reacted at 200-400° C. for 2-4 hours, cooled to room temperature, and finally the product is dispersed, washed, filtered and dried to obtain magnesium hydroxide whiskers;
[0022] The obtained magnesium hydroxide whiskers are successively treated with acid and alkali, and then calcined at 600-1000° C. for 2-5 hours, and then ultrafine ground and passed through a 1000-mesh sieve to obtain modified nano magnesium hydroxide whiskers;
[0023] The obtained modified nano magnesium hydroxide whisker and nano alumina sol are mixed and stirred evenly in a mass volume ratio of 1 g: 10-15 mL, and allowed to stand for 12-24 hours to obtain the metal sol-coated modified nano magnesium hydroxide whisker.
[0024] In a preferred embodiment of the present invention, the anhydrous ethanol is added in an amount according to a volume mass ratio of 0.5-1 mL:1 g to the basic magnesium sulfate whisker.
[0025] In a preferred embodiment of the present invention, the number average molecular weight of the polyethylene glycol is 2 to 4×10 4 The amount of polyethylene glycol added is 0.1 to 1 times the mass of the basic magnesium sulfate whisker.
[0026] In a preferred embodiment of the present invention, the acid treatment process is: immersing the magnesium hydroxide whiskers in a dilute hydrochloric acid solution with a concentration of 5 to 10 wt%, stirring at 40 to 60° C. for 30 to 40 minutes;
[0027] The alkali treatment process is as follows: immersing the acid-treated magnesium hydroxide whiskers in a sodium hydroxide solution with a concentration of 30-50 wt%, and stirring at room temperature for 1-2 hours.
[0028] In a preferred embodiment of the present invention, the organic alcohol is selected from one or a mixture of two or more of methanol, ethanol, isopropanol, n-butanol and isobutanol.
[0029] Another aspect of the present invention provides a use of the composite additive prepared according to the aforementioned preparation method in a fracturing acidizing process.
[0030] In a preferred embodiment of the present invention, the amount of the composite additive added to the fracturing fluid or acidizing fluid is 0.6-1.0 wt%.
[0031] By means of the above technical solution, the present invention has at least the following advantages:
[0032] 1. The composite surfactant of the present invention has N-fatty acyl amino acid surfactant as one of the main active ingredients, and is polymerized with humic acid / organosilane graft copolymer to obtain a composite surfactant with high chemical stability and thermal stability. The surfactant is firstly obtained by polymerizing humic acid and organosilicon monomer under the action of an initiator and a stabilizer to obtain a humic acid / organosilane graft copolymer, and then polymerized with N-fatty acyl amino acid surfactant to obtain a polymer. Compared with traditional surfactants, the obtained surfactant has higher surface activity, biodegradability and low pollution. At the same time, it can reduce the surface tension and interfacial tension of the system when used in the fracturing acidification process.
[0033] 2. Another active material of the present invention is a metal sol coated modified nano magnesium hydroxide whisker, which is prepared by coating modified nano magnesium hydroxide whisker with nano alumina sol, wherein the modified nano magnesium hydroxide whisker is a nano-scale material obtained by calcining magnesium hydroxide whisker after acid treatment and alkali treatment, and the surface of the modified nano magnesium hydroxide whisker is attached with a nano alumina sol coating through the coating effect of the nano alumina sol, and the obtained metal sol coated modified nano magnesium hydroxide whisker has high salt resistance. Therefore, the present invention can produce a synergistic effect between the composite surfactant and the metal sol coated modified nano magnesium hydroxide whisker by reasonably proportioning, and can significantly improve the effect of fracturing acidification treatment.
[0034] 3. The surfactant of the present invention can reduce the surface tension and interfacial tension of the system while improving the biodegradability of the product. The raw materials of the composite additive of the present invention are simple, and only contain surfactants and metal sol-coated modified nano magnesium hydroxide whiskers, organic alcohols and water. Through reasonable matching, an additive product with high demulsification rate and drainage rate is obtained. The composite additive of the present invention is used in the fracturing acidification process, which can significantly reduce the surface tension and interfacial tension, thereby improving the effect of fracturing acidification treatment.
[0035] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION
[0036] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0038] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0039] Unless otherwise specified, the nano-alumina sol used in the following examples is of model HN-ALJ03, purchased from Hangzhou Hengna New Materials Co., Ltd.
[0040] Unless otherwise specified, humic acid in the following examples was prepared by the following method: lignite was mixed with 45 wt % potassium hydroxide solution in a mass volume ratio of 1 g:15 mL and the mixture was reacted at 80° C. for 4 h to obtain the humic acid.
[0041] Embodiment 1:
[0042] Preparation of composite surfactant: Humic acid and methyltriethoxysilane were dispersed in a 20% acetone solution in a mass ratio of 1:1.5, and then azobisisobutyronitrile (the amount added was 0.02 times the mass of humic acid) and a number average molecular weight of 3×10 6 The mixture was stirred at 120°C for 6 hours under the action of polyvinyl pyrrolidone (the amount added was 0.003 times the mass of humic acid) to obtain a humic acid / methyltriethoxysilane graft copolymer. The humic acid / methyltriethoxysilane graft copolymer was mixed with fatty acyl lysine having a carbon number of 10 in a mass ratio of 1:2 and stirred at 110°C for 2.5 hours to obtain a composite surfactant.
[0043] Preparation of metal sol-coated modified nano magnesium hydroxide whiskers: basic magnesium sulfate whiskers were uniformly dispersed in deionized water, and then anhydrous ethanol (added in an amount according to a volume mass ratio of 0.75 mL: 1 g to basic magnesium sulfate whiskers) and a number average molecular weight of 3×10 4 The polyethylene glycol (the amount added is 0.5 times the mass of the basic magnesium sulfate whisker) is mixed evenly and placed in a high-pressure reactor, reacted at 300°C for 3h, cooled to room temperature after the reaction, and finally the product is dispersed, washed, filtered and dried to obtain magnesium hydroxide whiskers. The obtained magnesium hydroxide whiskers are first immersed in a dilute hydrochloric acid solution with a concentration of 8wt%, stirred at 50°C for 35min, then immersed in a sodium hydroxide solution with a concentration of 40wt%, stirred at room temperature for 1.5h, and calcined at 800°C for 3.5h after the above treatment, and finally ultra-finely ground and passed through a 1000 mesh sieve to obtain modified nano magnesium hydroxide whiskers. The obtained modified nano magnesium hydroxide whiskers are mixed and stirred evenly with nano alumina sol in a mass volume ratio of 1g:12mL, and allowed to stand for 18h to obtain the metal sol-coated modified nano magnesium hydroxide whiskers.
[0044] Preparation of composite additive for fracturing acidification: Mix composite surfactant, metal sol-coated modified nano magnesium hydroxide whisker and deionized water in a mass ratio of 1:0.75:2, stir at 35°C for 1.5h, then cool to room temperature, add isopropanol (the amount added is 0.2 times the mass of deionized water), stir and mix evenly, and obtain the composite additive for fracturing acidification.
[0045] Embodiment 2:
[0046] Preparation of composite surfactant: Humic acid and vinyl trimethoxysilane were dispersed in a 30% acetone solution in a mass ratio of 1:2, and then azobisisobutyronitrile (the amount added was 0.03 times the mass of humic acid) and a number average molecular weight of 1×10 6 The mixture was stirred at 100°C for 8 hours under the action of polyvinyl pyrrolidone (the amount added was 0.004 times the mass of humic acid) to obtain a humic acid / vinyl trimethoxysilane graft copolymer. The humic acid / vinyl trimethoxysilane graft copolymer was mixed with fatty acyl arginine having a carbon number of 10 in a mass ratio of 1:1 and stirred at 120°C for 1 hour to obtain a composite surfactant.
[0047] Preparation of metal sol-coated modified nano magnesium hydroxide whiskers: Disperse basic magnesium sulfate whiskers uniformly in deionized water, and then add anhydrous ethanol (in an amount of 0.5 mL: 1 g of basic magnesium sulfate whiskers by volume) and number average distribution
[0048] The sub-quantity is 2×10 4 The polyethylene glycol (the amount added is 0.5 times the mass of the basic magnesium sulfate whisker) is mixed evenly and placed in a high-pressure reactor, reacted at 400°C for 2h, cooled to room temperature after the reaction, and finally the product is dispersed, washed, filtered and dried to obtain magnesium hydroxide whiskers. The obtained magnesium hydroxide whiskers are first immersed in a dilute hydrochloric acid solution with a concentration of 10wt%, stirred at 40°C for 40min, then immersed in a sodium hydroxide solution with a concentration of 30wt%, stirred at room temperature for 2h, and after the above treatment, calcined at 1000°C for 2h, and finally ultra-finely ground and passed through a 1000 mesh sieve to obtain modified nano magnesium hydroxide whiskers. The obtained modified nano magnesium hydroxide whiskers are mixed and stirred evenly with nano alumina sol in a mass volume ratio of 1g:10mL, and allowed to stand for 24h to obtain the metal sol-coated modified nano magnesium hydroxide whiskers.
[0049] Preparation of composite additive for fracturing acidification: Mix composite surfactant, metal sol-coated modified nano magnesium hydroxide whisker and deionized water in a mass ratio of 1:0.5:1, stir at 40°C for 1 hour, then cool to room temperature, add n-butanol (the amount added is 0.1 times the mass of deionized water), stir and mix evenly, and obtain the composite additive for fracturing acidification.
[0050] Embodiment 3:
[0051] Preparation of composite surfactant: Humic acid and n-butyltrimethoxysilane were dispersed in a 10% acetone solution in a mass ratio of 1:1, and then azobisisobutyronitrile (the amount added was 0.01 times the mass of humic acid) and a number average molecular weight of 5×10 6 The mixture was stirred at 150°C for 4 hours under the action of polyvinyl pyrrolidone (the amount added was 0.002 times the mass of humic acid) to obtain a humic acid / n-butyltrimethoxysilane graft copolymer. The humic acid / n-butyltrimethoxysilane graft copolymer was mixed with fatty acyl histidine having a carbon number of 10 in a mass ratio of 1:3 and stirred at 100°C for 4 hours to obtain a composite surfactant.
[0052] Preparation of metal sol-coated modified nano magnesium hydroxide whiskers: Disperse basic magnesium sulfate whiskers uniformly in deionized water, and then add anhydrous ethanol (in an amount of 1 mL: 1 g of basic magnesium sulfate whiskers) and number average molecular weight
[0053] The amount is 4×10 4 The polyethylene glycol (the amount added is 0.5 times the mass of the basic magnesium sulfate whisker) is mixed evenly and placed in a high-pressure reactor, reacted at 200°C for 4 hours, cooled to room temperature after the reaction, and finally the product is dispersed, washed, filtered and dried to obtain magnesium hydroxide whiskers. The obtained magnesium hydroxide whiskers are first immersed in a dilute hydrochloric acid solution with a concentration of 5wt%, stirred at 60°C for 30 minutes, then immersed in a sodium hydroxide solution with a concentration of 50wt%, stirred at room temperature for 1 hour, and calcined at 600°C for 5 hours after the above treatment, and finally ultra-finely ground and passed through a 1000 mesh sieve to obtain modified nano magnesium hydroxide whiskers. The obtained modified nano magnesium hydroxide whiskers are mixed and stirred evenly with nano alumina sol in a mass volume ratio of 1g:15mL, and allowed to stand for 12 hours to obtain the metal sol-coated modified nano magnesium hydroxide whiskers.
[0054] Preparation of composite additive for fracturing acidification: Mix composite surfactant, metal sol-coated modified nano magnesium hydroxide whisker and deionized water in a mass ratio of 1:1:3, stir at 30°C for 2h, then cool to room temperature, add isobutanol (the amount added is 0.3 times the mass of deionized water), stir and mix evenly, and obtain the composite additive for fracturing acidification.
[0055] Comparative Example 1:
[0056] The surfactant in this comparative example is TF328 fluorocarbon surfactant.
[0057] Preparation of metal sol-coated modified nano magnesium hydroxide whiskers: basic magnesium sulfate whiskers were uniformly dispersed in deionized water, and then anhydrous ethanol (added in an amount according to a volume mass ratio of 0.75 mL: 1 g to basic magnesium sulfate whiskers) and a number average molecular weight of 3×10 4 The polyethylene glycol (the amount added is 0.5 times the mass of the basic magnesium sulfate whisker) is mixed evenly and placed in a high-pressure reactor, reacted at 300°C for 3 hours, cooled to room temperature after the reaction, and finally the product is dispersed, washed, filtered and dried to obtain magnesium hydroxide whiskers. The obtained magnesium hydroxide whiskers are first immersed in a dilute hydrochloric acid solution with a concentration of 8wt%, stirred at 50°C for 35 minutes, then immersed in a sodium hydroxide solution with a concentration of 40wt%, stirred at room temperature for 1.5 hours, and after the above treatment, calcined at 800°C for 3.5 hours, and finally ultra-fine ground and passed through 1000 mesh.
[0058] The modified nano magnesium hydroxide whisker was sieved to obtain the modified nano magnesium hydroxide whisker. The modified nano magnesium hydroxide whisker was mixed with the nano alumina sol in a mass volume ratio of 1 g:12 mL and stirred evenly, and allowed to stand for 18 hours to obtain the metal sol-coated modified nano magnesium hydroxide whisker.
[0059] Preparation of composite additive for fracturing acidification: TF328 fluorocarbon surfactant, metal sol-coated modified nano magnesium hydroxide whisker and deionized water are mixed in a mass ratio of 1:0.75:2, stirred at 35°C for 1.5h, then cooled to room temperature, and isopropanol (the amount added is 0.2 times the mass of deionized water) is added and stirred to mix evenly to obtain the composite additive for fracturing acidification.
[0060] Comparative Example 2:
[0061] The surfactant in this comparative example is fatty acyl lysine having 10 carbon atoms.
[0062] Preparation of metal sol-coated modified nano magnesium hydroxide whiskers: basic magnesium sulfate whiskers were uniformly dispersed in deionized water, and then anhydrous ethanol (added in an amount according to a volume mass ratio of 0.75 mL: 1 g to basic magnesium sulfate whiskers) and a number average molecular weight of 3×10 4The polyethylene glycol (the amount added is 0.5 times the mass of the basic magnesium sulfate whisker) is mixed evenly and placed in a high-pressure reactor, reacted at 300°C for 3h, cooled to room temperature after the reaction, and finally the product is dispersed, washed, filtered and dried to obtain magnesium hydroxide whiskers. The obtained magnesium hydroxide whiskers are first immersed in a dilute hydrochloric acid solution with a concentration of 8wt%, stirred at 50°C for 35min, then immersed in a sodium hydroxide solution with a concentration of 40wt%, stirred at room temperature for 1.5h, and calcined at 800°C for 3.5h after the above treatment, and finally ultra-finely ground and passed through a 1000 mesh sieve to obtain modified nano magnesium hydroxide whiskers. The obtained modified nano magnesium hydroxide whiskers are mixed and stirred evenly with nano alumina sol in a mass volume ratio of 1g:12mL, and allowed to stand for 18h to obtain the metal sol-coated modified nano magnesium hydroxide whiskers.
[0063] Preparation of composite additive for fracturing acidification: Fatty acyl lysine with a carbon number of 10, metal sol-coated modified nano magnesium hydroxide whiskers and deionized water are mixed in a mass ratio of 1:0.75:2, stirred at 35°C for 1.5h, then cooled to room temperature, and isopropanol (the amount added is 0.2 times the mass of deionized water) is added and stirred to mix evenly to obtain the composite additive for fracturing acidification.
[0064] Comparative Example 3:
[0065] Preparation of metal sol-coated modified nano magnesium hydroxide whiskers: basic magnesium sulfate whiskers were uniformly dispersed in deionized water, and then anhydrous ethanol (added in an amount according to a volume mass ratio of 0.75 mL: 1 g to basic magnesium sulfate whiskers) and a number average molecular weight of 3×10 4 The polyethylene glycol (the amount added is 0.5 times the mass of the basic magnesium sulfate whisker) is mixed evenly and placed in a high-pressure reactor, reacted at 300°C for 3h, cooled to room temperature after the reaction, and finally the product is dispersed, washed, filtered and dried to obtain magnesium hydroxide whiskers. The obtained magnesium hydroxide whiskers are first immersed in a dilute hydrochloric acid solution with a concentration of 8wt%, stirred at 50°C for 35min, then immersed in a sodium hydroxide solution with a concentration of 40wt%, stirred at room temperature for 1.5h, and calcined at 800°C for 3.5h after the above treatment, and finally ultra-finely ground and passed through a 1000 mesh sieve to obtain modified nano magnesium hydroxide whiskers. The obtained modified nano magnesium hydroxide whiskers are mixed and stirred evenly with nano alumina sol in a mass volume ratio of 1g:12mL, and allowed to stand for 18h to obtain the metal sol-coated modified nano magnesium hydroxide whiskers.
[0066] Preparation of composite additive for fracturing acidification: Mix metal sol-coated modified nano magnesium hydroxide whiskers with deionized water in a mass ratio of 0.75:2, stir at 35°C for 1.5h, then cool to room temperature, add isopropanol (the amount added is 0.2 times the mass of deionized water), stir and mix evenly, and obtain the composite additive for fracturing acidification.
[0067] Comparative Example 4:
[0068] Preparation of composite surfactant: Humic acid and methyltriethoxysilane were dispersed in a 20% acetone solution in a mass ratio of 1:1.5, and then azobisisobutyronitrile (the amount added was 0.02 times the mass of humic acid) and a number average molecular weight of 3×10 6 The mixture was stirred at 120°C for 6 hours under the action of polyvinyl pyrrolidone (the amount added was 0.003 times the mass of humic acid) to obtain a humic acid / methyltriethoxysilane graft copolymer. The humic acid / methyltriethoxysilane graft copolymer was mixed with fatty acyl lysine having a carbon number of 10 in a mass ratio of 1:2 and stirred at 110°C for 2.5 hours to obtain a composite surfactant.
[0069] Preparation of composite additive for fracturing acidification: Mix the composite surfactant and deionized water in a mass ratio of 1:2, stir at 35°C for 1.5h, then cool to room temperature, add isopropanol (the amount added is 0.2 times the mass of deionized water), stir and mix evenly, and obtain the composite additive for fracturing acidification.
[0070] Test Example 1: Basic performance testing of different composite additives
[0071] The composite additives prepared in the above Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to the following performance tests, wherein: the surface tension, interfacial tension, and drainage performance tests were tested with reference to SY / T5755-2016 "Performance Evaluation Method for Drainage Agents for Fracturing and Acidification"; the demulsification performance test was tested with reference to SY / T5280-2018 "General Technical Conditions for Crude Oil Demulsifiers"; the anti-swelling performance test was tested with reference to SY / T5971-2016 "Performance Evaluation Method for Clay Stabilizers for Fracturing, Acidification and Water Injection in Oil and Gas Fields".
[0072] The test results are shown in Table 1.
[0073] Table 1 Statistics of performance test results of different additives
[0074]
[0075]
[0076] As can be seen from the results of Table 1, the composite additives of Examples 1 to 3 of the present invention have lower surface tension and interfacial tension, as well as higher drainage aid rate, dehydration rate and anti-swelling rate. As can be seen from Comparative Examples 1 and 2, compared with the common TF328 fluorocarbon surfactant, the additive performance obtained by using fatty acyl lysine with a carbon number of 10 as a surfactant is poor. By comparing Examples 3 and 4, it can be seen that the performance of the additive using only one of the active substances of the present invention (composite surfactant or metal sol coated modified nano magnesium hydroxide whisker) is significantly reduced. By comparing Example 1 with Comparative Examples 1 to 4, it can be seen that the use of composite surfactant or metal sol coated modified nano magnesium hydroxide whisker can play a synergistic role, which can reduce the surface tension and interfacial tension to a certain extent, and improve the drainage aid rate, dehydration rate and anti-swelling rate at the same time.
[0077] Test Example 2: Application of different composite additives in acid fracturing fluid
[0078] According to the formula of Table 2, an acid fracturing fluid was prepared, wherein the demulsifier and drainage aid in the acid fracturing fluid used the composite additives prepared in Example 1 and Comparative Examples 1 to 4, respectively. The total mass percentage of each formula was 100%, and the specific formula composition and content were as follows:
[0079] Table 2 Formula and content of acid fracturing fluid
[0080] raw material Percentage content (%) 25wt% hydrochloric acid 15 15wt% hydrofluoric acid 5.0 Sodium Carboxymethyl Cellulose 0.15 Gum Arabic 0.1 Imidazoline corrosion inhibitor DRKJ-12 2.0 Demulsifier 0.8 Sodium Citrate 0.15 water margin
[0081] The preparation method of the acid fracturing fluid is as follows: 25wt% hydrochloric acid, 15wt% hydrofluoric acid, imidazoline corrosion inhibitor DRKJ-12, demulsifier, drainage aid, sodium citrate and water are mixed evenly in proportion, and then sodium carboxymethyl cellulose and gum arabic are added and stirred evenly to obtain the acid fracturing fluid.
[0082] The above acid fracturing fluid was used in a fracturing test in a certain oil field: different acid fracturing fluids were injected into the heavy oil production process of a certain oil field, and the oil recovery rate was finally calculated. The results are shown in Table 3.
[0083] Oil recovery rate = recoverable reserves / proven reserves*100%,
[0084] Among them, recoverable reserves = proven reserves * recoverable rate - mined reserves.
[0085] Table 3 Oil recovery rate produced by different acid fracturing fluids
[0086] serial number Oil recovery rate (%) Acid fracturing fluid prepared in Example 1 35.58 Acid fracturing fluid prepared in Comparative Example 1 30.82 Acid fracturing fluid prepared in Comparative Example 2 29.13 Acid fracturing fluid prepared in comparative example 3 20.94 Acid fracturing fluid prepared in comparative example 4 25.67
[0087] It can be seen from the results in Table 3 that, compared with Comparative Examples 1 to 4, the acid fracturing fluid prepared in Example 1 of the present invention can significantly improve the oil recovery rate.
[0088] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite additive for fracturing acidification, characterized in that: The method comprises the following steps: The composite surfactant, the metal sol-coated modified nano magnesium hydroxide whisker and deionized water are mixed in a mass ratio of 1:0.5-1:1-3, stirred at 30-40° C. for 1-2 hours, then cooled to room temperature, and organic alcohol is added and stirred to mix uniformly to obtain the composite additive for fracturing acidification; Wherein, the amount of the organic alcohol added is 0.1 to 0.3 times the mass of deionized water; The preparation process of the composite surfactant is as follows: Disperse humic acid and organosilicon monomer in a mass ratio of 1:1-2 in an acetone solution with a volume fraction of 10-30%, and then stir and react at 100-150°C for 4-8h under the action of an initiator and a stabilizer to obtain a humic acid / organosilane graft copolymer; The humic acid / organosilane graft copolymer and the N-fatty acyl amino acid surfactant are mixed in a mass ratio of 1:1-3, and stirred at 100-120° C. for 1-4 hours to obtain a composite surfactant; The preparation process of the metal sol-coated modified nano magnesium hydroxide whisker is as follows: The basic magnesium sulfate whiskers are uniformly dispersed in deionized water, and then anhydrous ethanol and polyethylene glycol are added in sequence and mixed evenly, and then placed in a high-pressure reactor, reacted at 200-400° C. for 2-4 hours, cooled to room temperature, and finally the product is dispersed, washed, filtered and dried to obtain magnesium hydroxide whiskers; The obtained magnesium hydroxide whiskers are successively treated with acid and alkali, and then calcined at 600-1000°C for 2-5 hours, and then ultrafine ground and passed through a 1000-mesh sieve to obtain modified nano magnesium hydroxide whiskers; The obtained modified nano magnesium hydroxide whisker and nano alumina sol are mixed and stirred evenly in a mass volume ratio of 1 g: 10-15 mL, and allowed to stand for 12-24 hours to obtain the metal sol-coated modified nano magnesium hydroxide whisker.
2. The preparation method according to claim 1, characterized in that: The humic acid is prepared by mixing lignite with 30-60wt% potassium hydroxide solution in a mass volume ratio of 1g:10-20mL and reacting at 70-90°C for 2-5h.
3. The preparation method according to claim 1, characterized in that: The organosilicon monomer is selected from one or a mixture of two or more of methyltriethoxysilane, methyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, n-butyltrimethoxysilane, n-butyltriethoxysilane, isobutyltriethoxysilane and isobutyltrimethoxysilane.
4. The preparation method according to claim 1, characterized in that: The initiator is selected from one or a mixture of two or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutyramidine hydrochloride, and azobisisobutylimidazoline hydrochloride, and the added amount of the initiator is 0.01 to 0.03 times the mass of humic acid.
5. The preparation method according to claim 1, characterized in that: The stabilizer has a number average molecular weight of 1×10 6 ~5×10 6 The amount of polyvinyl pyrrolidone added is 0.002 to 0.004 times the mass of humic acid.
6. The preparation method according to claim 1, characterized in that: The N-fatty acyl amino acid surfactant is any one of fatty acyl lysine, fatty acyl arginine and fatty acyl histidine with a carbon number between 4 and 16, or a mixture of two or more thereof.
7. The preparation method according to claim 1, characterized in that: The anhydrous ethanol is added in an amount of 0.5-1 mL:1 g of the basic magnesium sulfate whisker volume mass ratio; the number average molecular weight of the polyethylene glycol is 2-4×10 4 The amount of polyethylene glycol added is 0.1 to 1 times the mass of the basic magnesium sulfate whisker.
8. The preparation method according to claim 1, characterized in that: The acid treatment process is as follows: immersing the magnesium hydroxide whisker in a dilute hydrochloric acid solution with a concentration of 5-10wt%, and stirring at 40-60°C for 30-40min; The alkali treatment process is as follows: immersing the acid-treated magnesium hydroxide whiskers in a sodium hydroxide solution with a concentration of 30-50 wt%, and stirring at room temperature for 1-2 hours.
9. The preparation method according to claim 1, characterized in that: The organic alcohol is selected from one of methanol, ethanol, isopropanol, n-butanol, and isobutanol, or a mixture of two or more thereof.
